Clinical studies on cellular and biochemical constituents of rumen liquor and blood in cattle - Sabry Ahmed Mousa Shehata; Abdelmonem Abdelfattah Abdelsamee; Ibrahim Abdelsattar Saleh; Taher Ahmad Baraka (Cairo : Sabry Ahmed Mousa Shehata, 2011)
The present study was carried out on 109 dairy cattle , 108 fattening calves , 16 dairy cattle suffering from simple indigestion , 11 fattening calves suffering from rumen acidosis and 13 dairy cattle suffering from forthy tympany belong to different private farms from different localities and different ages all cases were exposed to comprehensive clinical examination , blood and rumen liquor samples were taken from animals for studying the effect of seasons of year , stages of lactation and diseased cases on physical clinical examination
Thesis (Ph.D.) - Cairo University - Faculty of Veterinary Medicine - Department of Internal Medicine Infections diseases
Issued also as CD
Keywords: Blood constituents; Dairy cattle; Fattening calves